Birth weight was associated with maternal exposure to intimate partner violence during pregnancy in southern Ethiopia: A prospective cohort study - Belay, Sewhareg; Astatkie, Ayalew; Hinderaker, Sven Gudmund (Frontiers in Public Health, 2022)
Introduction: Birth weight is defined as the first weight of the newborn, ideally measured soon after birth. A recent Ethiopian survey estimated that 48% of births took place in health institutions. Data for women exposed to intimate partner violence (IPV) may be lacking in official statistics as these women may prefer to deliver at home, where data from non institutional births are not routinely recorded, including reporting of birth weights. Objective: The aim of this study was to investigate the association between maternal exposure to IPV during pregnancy, and birth weight in a community in Wondo Genet district, southern Ethiopia. Methods: We carried out a community based prospective cohort study February to December, 2017. We followed up 505 pregnant women until after delivery, and their newborns. An interview about partner violence was done during pregnancy. The birth weight of each baby was measured in grams by field assistants visiting the homes. Twins and late birth weight measurements were excluded. Factors associated with birth weight were assessed by multiple linear regression. Results: Birth weight was assessed within 48 hours for 477 (94.5%) newborns, and between 48 and 72 hours for an additional 28 (5.5%). There were 365 (72.3%) institutional deliveries. In an adjusted regression analysis (IPV adjusted for socio-economic status), birth weight was 202g (95% CI 85 to 319) lower among newborns of women exposed to IPV than among the unexposed. Birth weight was also lower among girls than boys, among newborns delivered at home than at health facility, and among babies with a younger gestational age. Conclusions: Maternal exposure to IPV during pregnancy was associated with lower birth weights for the baby. Antenatal clinics should consider routinely identifying women suffering from IPV and identifying babies with lower birth weights at home is an important indicator.